Impinging jet micromixer for flow synthesis of nanocrystalline MgO: role of mixing/impingement zone - Kumar, D. V. Ravi; Bhagavatula L. V. Prasad; Kulkarni, A. A. (Industrial & Engineering Chemistry Research, 2013)
Continuous flow synthesis of nanomaterials via sol-gel process using microreactors has not received much attention. For the synthesis of gels where the reaction time is of the order of few seconds to few tens of seconds, microchannel reactors are an excellent processing option. However since a `gel' does not `flow' easily, making it in a microchannel usually clogs the microchannel. We envisaged that by using an impinging jet micromixer, where the two reactants impinge and collide to form a mixing zone outside the micromixer, this problem could be circumvented. Here we report a successful implementation of continuous flow synthesis of metal oxides formed by the rapid sol-gel process taking the nanocrystalline MgO (NC-MgO) as a specific example. Furthermore, we clearly demonstrate that the nature of the mixing zone formed by the impinging jets governs the surface area of the product. Specific flow rate and impingement angle are identified that yield high surface area materials.